2007
DOI: 10.1111/j.1469-8137.2007.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycosylation affects substrate specificity of chicory fructan 1‐exohydrolase: evidence for the presence of an inulin binding cleft

Abstract: Summary• Recently, the three-dimensional structure of chicory ( Cichorium intybus ) fructan 1-exohydrolase (1-FEH IIa) in complex with its preferential substrate, 1-kestose, was determined. Unfortunately, no such data could be generated with high degree of polymerization (DP) inulin, despite several soaking and cocrystallization attempts.• Here, site-directed mutagenesis data are presented, supporting the presence of an inulin-binding cleft between the N-and C-terminal domains of 1-FEH IIa. In general, enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…S4 at JXB online). Additional evidence was generated with enzyme reactions containing either chicory 1-FEH (fructan-1-exohydrolase) IIa (Le Roy et al ., 2007) or sugar beet 6-FEH (Van den Ende et al ., 2003) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…S4 at JXB online). Additional evidence was generated with enzyme reactions containing either chicory 1-FEH (fructan-1-exohydrolase) IIa (Le Roy et al ., 2007) or sugar beet 6-FEH (Van den Ende et al ., 2003) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Kusch et al (2009) recently demonstrated that numerous biochemical factors (including Ca 2+ signalling, protein kinases, and phosphatases) are directly involved in the modulation of the expression of the gene encoding 1-FFT. Similarly, the FEH enzyme activity depends on three distinct isoforms (1-FEHI, IIa, and IIb) that may exhibit various patterns of regulation (Van Laere and Van den Ende, 2002; Van den Ende et al, 2004; Le Roy et al, 2007; Kusch et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…For the A . thaliana cell wall invertase 1-FEH IIa, N -glycosylation has been shown to be critical for maintaining both enzyme stability and its optimal conformation [52]. We therefore hypothesized that glycosylation modification is involved in the sucrose metabolism possibly by regulating the enzyme activity of key regulators such as CIN2/GIF1.…”
Section: Discussionmentioning
confidence: 99%